2016
DOI: 10.1016/j.bpj.2015.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Nesprin-2G, a Component of the Nuclear LINC Complex, Is Subject to Myosin-Dependent Tension

Abstract: The nucleus of a cell has long been considered to be subject to mechanical force. Despite the observation that mechanical forces affect nuclear geometry and movement, how forces are applied onto the nucleus is not well understood. The nuclear LINC (linker of nucleoskeleton and cytoskeleton) complex has been hypothesized to be the critical structure that mediates the transfer of mechanical forces from the cytoskeleton onto the nucleus. Previously used techniques for studying nuclear forces have been unable to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
170
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 186 publications
(179 citation statements)
references
References 53 publications
6
170
1
Order By: Relevance
“…As myosin-generated cellular contractile forces can be exerted on the nuclear surface through the LINC complex141733, we asked whether non-muscle myosin II inhibition has similar effects on gene expression as with LINC complex disruption. Because myosin forces are small in cells on the soft substrate1734, we inhibited myosin activity on the stiff substrate with blebbistatin or with Y27632 (a Rho-kinase inhibitor, hereafter called Y27) in control KDEL cells (we have validated myosin inhibition with this approach in NIH 3T3 fibroblasts elsewhere1227; see also Supplementary Figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As myosin-generated cellular contractile forces can be exerted on the nuclear surface through the LINC complex141733, we asked whether non-muscle myosin II inhibition has similar effects on gene expression as with LINC complex disruption. Because myosin forces are small in cells on the soft substrate1734, we inhibited myosin activity on the stiff substrate with blebbistatin or with Y27632 (a Rho-kinase inhibitor, hereafter called Y27) in control KDEL cells (we have validated myosin inhibition with this approach in NIH 3T3 fibroblasts elsewhere1227; see also Supplementary Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…However, our identification of genes that are common to myosin inhibition and LINC disruption suggests a list of genes that likely depend directly on actomyosin tension exerted on the nucleus143356 for their mechanosensitivity. We have previously shown that SUN1L expression softens the integrated nucleus-cytoskeleton in fibroblasts25, which likely indicates altered forces on the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion is consistent with the findings of other recent studies. For example, a nesprin-2-based actin tension sensor revealed that static nuclei of mouse and human fibroblasts are under constant actomyosin force [45] and local displacement of nuclei by microneedles showed cytoskeletal dependent restoring forces [31, 32]. Also, in both the differentiation of mouse embryonic stem cells and early Drosophila development, nuclei are reported to be prestressed as their shape is altered by disrupting cytoskeletal elements [46].…”
Section: Discussionmentioning
confidence: 99%
“…These force sensors utilize two fluorescent proteins that are able to exchange energy through non-radiative transfer (FRET), separated with a short unstructured or structured peptide. These genetically encoded force sensors have been incorporated into spectrin proteins (115), vinculin and talin (116, 117), and nuclear nesprins (118), all of which are subject to tension from intracellular stress fibers. As the tension on the protein containing the force sensor increases, the FRET donor and acceptor separate and the FRET ratio decreases.…”
Section: Testable Predictions and The Techniques To Examine Themmentioning
confidence: 99%